2018
DOI: 10.1007/s11145-018-9879-9
|View full text |Cite
|
Sign up to set email alerts
|

Children’s integration of information across texts: reading processes and knowledge representations

Abstract: Constructing a knowledge representation from multiple texts requires the integration of information across texts. The aim of the current study was to investigate how elementary school students integrate information across multiple text passages and, particularly, whether students use information from a prior text to improve understanding of a current text. A sample of 105 children in grades 4 and 6 participated in the experiment. The multiple-text integration paradigm was used to study integration processes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
(88 reference statements)
0
12
0
2
Order By: Relevance
“…Furthermore, we were interested in how MDC test scores are related to final school exam grades, the level of university studies and university performance. Since MDC is a competence that can already be observed in upper elementary school children (Beker et al, 2019;Florit et al, 2019) and develops further during the course of university studies (von der Mühlen et al, 2016; Schoor et al, 2020b), we expected that MDC test scores. .…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we were interested in how MDC test scores are related to final school exam grades, the level of university studies and university performance. Since MDC is a competence that can already be observed in upper elementary school children (Beker et al, 2019;Florit et al, 2019) and develops further during the course of university studies (von der Mühlen et al, 2016; Schoor et al, 2020b), we expected that MDC test scores. .…”
Section: The Present Studymentioning
confidence: 99%
“…Nevertheless, even high school graduates should be able to extract the meaning of multiple documents, analyze and evaluate their content and employ the texts in their own learning process (Common Core State Standards, 2010;Kultusministerkonferenz, 2012). Studies suggest that upper elementary school children are already capable of processing multiple documents (Beker et al, 2019;Florit et al, 2019). Schoor et al (2020b) found that the MDC of university students correlated statistically significant with their final school exam grades, indicating that high-performing students performed better in an MDC test than low-performing students.…”
Section: Multiple Document Comprehensionmentioning
confidence: 99%
“…Structuring of educational texts is the process of presenting a certain fragment of scientific knowledge in a speech work. As a result, educational texts, on the one hand, implement the goal of science -"objective description, explanation and forecast of processes and phenomena of reality" [9, p. 108], on the other -the didactic task of presenting knowledge (fact, concept, regularity, method, idea) as a component of the content of training, a necessary component of the information field of the educational field, which the student considers as a comprehensible information space [10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…surface model of single texts, intertext model, and integrated situation model). Overall, the results seem to suggest that working memory is involved in surface comprehension of single texts (Braasch et al, 2014 ; Mason et al, 2017 ; Beker et al, 2019 ). Conversely results about the involvement of working memory at the integrated situation model are mixed (Braasch et al, 2014 ; Beker et al, 2019 ; Florit et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…Overall, the results seem to suggest that working memory is involved in surface comprehension of single texts (Braasch et al, 2014 ; Mason et al, 2017 ; Beker et al, 2019 ). Conversely results about the involvement of working memory at the integrated situation model are mixed (Braasch et al, 2014 ; Beker et al, 2019 ; Florit et al, 2020 ). The studies which assessed intertextual integration share several differences, making it difficult to draw an even tentative interpretation: sample (upper-secondary school students or primary school students); task (prompted open question or recall) and medium (written responses or oral responses).…”
Section: Discussionmentioning
confidence: 96%